Handbook of research on behavioral finance and investment strategies decision making in the financial industry - Copur, Zeynep 1968- (Business Science Reference, 2015)
"This book presents an interdisciplinary, comparative, and competitive analysis of the thought processes and planning necessary for individual and corporate economic management"-- Provided by publisher.